Printing and disciplinary forms: manuals of confessors in the face of nefarious sin (16th-18th centuries) - Ruiz Astiz, Javier (Huarte de San Juan. Geografía e Historia, 2022)
During the Old Regime, there was a prominent interest on the part of the religious authorities to control popular morality. Among those deviant behaviors, sinful sexual practices stand out, such as nefarious sin. To achieve this ambitious purpose they used different ways thanks to the possibilities offered by the printing press. The moralizing printed matter, where the confessors manuals were included, sought to indoctrinate and correct these attitudes. Thus, the objective of this study is to review the different manuals that were published between the 16th and 18th centuries in the Iberian Peninsula to censor sodomy and bestiality.
Keywords: Printing; Old book; Confessors’ manuals; Nefarious sin; Old Regime